Massive Myocardial Infarction in a Full-Term Newborn: A Case Report. (16th May 2010) - Fesslova, Vlasta; Lucci, Gina; Brankovic, Jelena; Cordaro, Stefania; Caselli, Emilio; Moro, Guido
Abstract : A full-term female newborn with neonatal asphyxia and severe anemia (Hb 2.5 g/dL) with normal heart developed a massive myocardial infarction. No examinations were performed during pregnancy for parental nomadism. The baby had immediate external cardiac massage, ventilatory assistance, and blood transfusion. Cardiomegaly was evident at chest X-ray and marked signs of ischemia-lesion at ECG. Echocardiography showed dilated, hypertrophic, and hypocontractile left ventricle (LV), mitral and tricuspid regurgitation, and moderate pericardial effusion. Rh isoimmunization and infective agents were excluded at laboratory tests. Despite the treatment with inotropes, hydrocortisone, and furosemide, the baby worsened and died at 45 hours of life. Postmortem examination showed diffuse subendocardial infarction of LV and diffuse parenchymal hemorrhages and myocardial hypertrophy, increase of eosinophilia, and polymorphonucleated cells at histology. Our patient suffered apparently from longstanding fetal anemia of unknown etiology that led to perinatal distress, severe hypoxia, and massive myocardial infarction, unresponsive to the therapy.